Protection of potato against scab - Shovkun, I. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
The results of studies to determine the effectiveness of chemical and biological preparations for potato scab development are presented. Their positive influence on potato yield is shown. It has been established that the use of fungicides and biologics for the presowing treatment of tubers, somewhat limits the development of ordinary scab. The highest efficiency for two years of observations was noted with the use of fungicides Rovral Aquaflo 500 and Serkadis.